Analisis Produktivitas dan Efektivitas Pada Pembuatan Alat Pengupas Kulit Kelapa Muda - Ximenes, Heskey Kurniawan; Purnama, Jaka (Fakultas Teknik Universitas Tulang Bawang, 2025)
This study aims to design and analyze a young coconut skin peeling tool to improve efficiency and safety in the coconut-cutting process, which is currently done manually. The manual process, which takes an average of 3 minutes per coconut, is potentiallyinefficient and risky. With the development of this tool, it is expected to speed up the peeling process, increase productivity, and support the growth of Pak Agung's business in Sidoarjo Regency. The methods used in this study include productivity analysis and effectiveness analysis of the tool. The productivity analysis was conducted by calculating the time required to peel a certain number of coconuts before and after the use of the tool, while the effectiveness analysis evaluates how much the tool can reduce processing time and increase the number of coconuts that can be processed in a unit of time. The analysis results show that after using the tool,the time needed to peel 30 coconuts was reduced from 95 minutes to only 16 minutes, and the processing time per coconut dropped from 3 minutes to 32 seconds. This achievement shows a significant improvement, reflecting better operationalefficiency. This study emphasizes the importance of innovation in tools and technology to support the sustainability of micro and small businesses, as well as to contribute positively to the performance of the coconut processing industry. Keywords: Cost Analysis, Effectiveness, Productivity, Product Design